Improved Berezin—Li—Yau inequalities with magnetic field. Issue 1 (30th January 2015) - Kovařík, Hynek; Weidl, Timo
Abstract : In this paper we study the eigenvalue sums of Dirichlet Laplacians on bounded domains. Among our results we establish an improvement of the Berezin bound and of the Li—Yau bound in the presence of a constant magnetic field previously obtained by Erdős et al . and Melas.